2021
DOI: 10.3389/fonc.2021.637871
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Autoantibodies Based on the Human Proteomic Chips and Evaluation of Their Performance in the Detection of Gastric Cancer

Abstract: Autoantibodies against tumor-associated antigens (TAAbs) can be used as potential biomarkers in the detection of cancer. Our study aims to identify novel TAAbs for gastric cancer (GC) based on human proteomic chips and construct a diagnostic model to distinguish GC from healthy controls (HCs) based on serum TAAbs. The human proteomic chips were used to screen the candidate TAAbs. Enzyme-linked immunosorbent assay (ELISA) was used to verify and validate the titer of the candidate TAAbs in the verification cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…In this study, the range of the AUC of a single autoantibody was 0.617–0.716, which was difficult to meet the requirements for early diagnosis in clinical practice. By establishing the logistic regression predictive model, which was widely used to classify diseases, especially in cancers ( Wang S et al, 2018 ; Cui et al, 2021 ), it proved to be a conventional analytical method. This model contained three biomarkers finally, and the sensitivity, specificity, Youden index, accuracy, and AUC of this model were 70.59%, 86.27%, 0.5686, 78.43%, and 0.798, respectively, between OS and NHS.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the range of the AUC of a single autoantibody was 0.617–0.716, which was difficult to meet the requirements for early diagnosis in clinical practice. By establishing the logistic regression predictive model, which was widely used to classify diseases, especially in cancers ( Wang S et al, 2018 ; Cui et al, 2021 ), it proved to be a conventional analytical method. This model contained three biomarkers finally, and the sensitivity, specificity, Youden index, accuracy, and AUC of this model were 70.59%, 86.27%, 0.5686, 78.43%, and 0.798, respectively, between OS and NHS.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies showed that combining multiple biomarkers can remarkably improve the diagnostic accuracy and speci city in different cancerous diseases, such as OC, BC, ESCC, gastric cancer (GC) and LC [17,[21][22][23][24][25]. Jiang et al utilized decision tree method to construct a diagnostic panel consist of seven TAAbs (TP53, NPM1, FGFR2, PIK3CA, GNA11, HIST1H3B, and TSC1) with the AUC of 0.897 and sensitivity and speci city of 94.4% and 84.9% [17].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, WGCNA is an excellent algorithm in screening the biological markers, and it has been used in many studies 26 . The human proteomics chip contains 21 000 human recombinant proteins in this study, which can comprehensively screen TAAs 53‐56 . In summary, bioinformatics can screen for genes that play important roles in the occurrence and development of HCC.…”
Section: Discussionmentioning
confidence: 99%
“… 26 The human proteomics chip contains 21 000 human recombinant proteins in this study, which can comprehensively screen TAAs. 53 , 54 , 55 , 56 In summary, bioinformatics can screen for genes that play important roles in the occurrence and development of HCC. Hence, those two methods were used together to screen valuable TAAs as much as possible.…”
Section: Discussionmentioning
confidence: 99%